Sociology and history in the work of Mirko Kosić: eight decades later - Jovanović, Ivan М (Sociološki pregled, 2018)
This work is focused on examining the relationship between two sciencesnamely sociology and history. Although the latter can be treated in various ways, it is perceived through the lenses of the sociological work of Mirko M. Kosić. This view is outlined with the analogy of the work of the above named sociologist with his contemporaries, with the work of present day sociologists, namely, with the pen of the authorities from the field of sociology, history and historical sociology. His view of the relationship between two sciences is beyond dispute, intrinsically understandable, although there were authors that were adherents of diametrically different viewpoint short period after his agency. The main finding of this rethinking is that our first learned sociologist is one of the founders of historical sociology in Serbia, but nonetheless he is neither the only nor the most important. Nevertheless, what is valid for the opus of our sociologist in general, and that is a reasonable degree of neglect, deflection, applies to this question as well. This is, however, marked in bold and accentuated as the result of the conclusion. Finally, this piece of writing in itself is doing away with certain conjectures that exist in our sociological avant-garde.Кeywords: sociology, history, Mirko M. Kosić , historical sociology